Study of dark current in mid-infrared InAsSb-based hetero n-i-p photodiode - Suo, Fei (2020)
In this work, we study the dark current characteristics in middle-wavelength infrared photodiodes with a heterojunction n-i-p architecture. The photodiode includes wide bandgap and quaternary layers to reduce the bulk dark current. Photodiodes with square mesa size varying from 500-20 μm are fabricated and their dark currents are characterized at temperatures from 77 K to room temperature (293 K). Surface leakage current is found to be negligible under normal operational conditions. Based on the study of activation energy, when the magnitude of reverse bias is smaller than 0.1 V and the temperature is larger than 255 K, the bulk dark current is found to be dominated mainly by the diffusion process. The contribution from the Shockley-Read-Hall and tunneling process will become significant when the temperature is below 255 K or the magnitude of reverse voltage bias is larger than 0.1 V. At -0.1 V bias, the observed dark current density is as small as 0.605 A • cm-2 at room temperature, and decreases to 6.6 × 10-2 A • cm-2 at 255 K and 1.16 × 10-3 A • cm-2 at 185 K for a typical square mesa diode with a size of 50 μm. Room-temperature performance of the photodiode demonstrates a cutoff wavelength of 5 μm and a blackbody detectivity of 1.5 × 109 cm • Hz1/2 W-1.